2014
DOI: 10.1016/j.jns.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

IncobotulinumtoxinA (Xeomin®) injected for blepharospasm or cervical dystonia according to patient needs is well tolerated

Abstract: Typically, botulinum toxin injections for blepharospasm or cervical dystonia (CD) are administered at approximately 3-month intervals, reflecting concerns that shorter intervals might increase the risk of adverse events (AEs) and development of neutralizing antibodies. These post-hoc analyses investigated flexible incobotulinumtoxinA (Xeomin ® ) injection intervals (6-20 weeks) in patients with blepharospasm or CD. Patients received up to 6 injections at intervals ≥6 weeks, as determined by physician assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
0
33
0
6
Order By: Relevance
“…Since several patients have benefit duration shorter than 12 weeks, it is necessary to do studies to establish whether more flexible schedules, with shorter intervals might be safe in terms of immunogenicity. A recent paper found that intertreatment intervals as short as 6 weeks are safe for up to 2 years of follow up in patients with CD or blepharospasm treated with A/ Inco (Evidente et al, 2014). However, in this series, patients were treated with fixed doses, which were somewhat lower (not exceeding 50U for blepharospasm and 120e240U for CD), than used in clinical practice.…”
Section: Blepharospasm and Hemifacial Spasmmentioning
confidence: 85%
See 1 more Smart Citation
“…Since several patients have benefit duration shorter than 12 weeks, it is necessary to do studies to establish whether more flexible schedules, with shorter intervals might be safe in terms of immunogenicity. A recent paper found that intertreatment intervals as short as 6 weeks are safe for up to 2 years of follow up in patients with CD or blepharospasm treated with A/ Inco (Evidente et al, 2014). However, in this series, patients were treated with fixed doses, which were somewhat lower (not exceeding 50U for blepharospasm and 120e240U for CD), than used in clinical practice.…”
Section: Blepharospasm and Hemifacial Spasmmentioning
confidence: 85%
“…In all series, dry mouth and dysphagia are the most common side effects. In most studies a high rate of secondary failure is also reported, moreover, an early vanishing of effects has been reported (Factor et al, 2005), and a shorter duration of the effects, when compared to BoNT/A has been reported ( Table 2).…”
Section: Cervical Dystoniamentioning
confidence: 99%
“…IncobotulinumtoxinA is the only formulation studied in clinical trials allowing flexible dosing intervals. These studies showed that incobotulinumtoxinA for the treatment of CD can be effective and well tolerated when administered using flexible schedules with minimum injection intervals of 6 weeks26,27 or 10 weeks 28. Importantly, in these studies incobotulinumtoxinA injections were administered on the basis of clinical need and following physical and neurological examinations by the investigator, who assessed disease severity using clinical rating scales.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with aboBTXA half of the patients treated with a dosage of 250 MU and 39% of treated with a dosage of 500 MU required reinjection after only 8 weeks [47]. In a study of patients with CD treated with fixed dosages of 120 or 240 MU incoBTXA, repeated injections at flexible intervals of 6-20 weeks per patients' needs did not show increased safety concerns with b 12 weeks compared with N12 weeks intervals [48].…”
Section: Inter-injection Intervalmentioning
confidence: 92%